Pengaruh Efikasi Diri, Motivasi Kerja, dan Pengalaman Magang Terhadap Kesiapan Kerja Mahasiswa FEBI IAIN Ponorogo - Eka Nurwidi Astuti; Muhtadin Amri (Niqosiya: Journal of Economics and Business Research, 2024)
This research aims to determine and analyze the influence of self-efficacy, work motivation, and internship experience on the work readiness of FEBI IAIN Ponorogo students. This research used quantitative methods and data collection techniques by distributing questionnaires to 250 active FEBI IAIN Ponorogo class 2018-2020 students. Multiple linear regression was used in this research as a data analysis technique with stages of validity, reliability, descriptive analysis, classical assumption testing, and hypothesis testing. This research shows that self-efficacy positively and significantly affects work readiness. Work motivation has a positive and significant effect on work readiness. Internship experience has a positive and significant effect on work readiness. Self-efficacy, work motivation, and internship experience simultaneously influence the work readiness of FEBI IAIN Ponorogo students. The test results for the coefficient of determination value are shown by the R² value, namely 0.582 or 58.2%, which means that the contribution of all independent variables, namely self-efficacy, work motivation, and internship experience, can explain the dependent variable, namely work readiness, of 58.2%. In comparison, other factors influence the remaining 41.8%.